Representações do fascismo na HQ "Maus: a história de um sobrevivente." - Santana Júnior, Eduardo José de (2025)
This dissertation investigates the representations of fascism in the comic book "Maus" (1987; 1995), by Art Spiegelman, articulating the theories of Maurice Halbwachs (1990) about collective memory, Roger Chartier (1988; 1991; 2010) about cultural representations and the analyzes of Robert Paxton (2004), Theodor Adorno (2020) and Umberto Eco (2018) on fascist dynamics. The research starts from Halbwachs's premise that memory is a socially constructed phenomenon, mediated by social frameworks and perception schemes. The artwork is analyzed as a cultural and historical artifact located at the intersection between individual and collective memory, operating as a critical device to unveil practices and representations of fascist discourses. It is demonstrated that “Maus” transcends historical testimony by revealing, through graphic and narrative strategies, the persistence of fascism as a political-cultural phenomenon. The articulation between visual analysis and critical theory reinforces the potential of comic books as instruments to confront authoritarian legacies, contributing to studies on memory, representation and visual culture. Methodologically, the research combines structural, contextual and qualitative analysis, expanding previous approaches (Chico, 2020) and incorporating the observation of paratextual elements and complete narrative sequences (Luca, 2020). The fragmentation of the narrative, with the alternation of times and voices between Vladek and Art, illustrates memory as a dialogical reconstruction. By examining fascism as a dynamic and adaptable movement, a theoretical framework is established to understand its representation in "Maus", not only as a historical reconstruction, but also as a reflection about ideological mobilization and systemic violence. We consider "Maus" a critical mirror: through the language of comic books, we identify, contextualize and analyze fascist rhetoric. Thus, we demonstrate that the fight against the rise of the extreme right wing is not a closed chapter of history, but a permanent ethical challenge. Finally, we invite readers to recognize, in "Maus", the mechanisms of oppression and violence that continue to reinvent themselves incontemporary societies.